Comparative study on optimization of factors affecting epoxidation-hydroxylation reaction for the production of waste cooking oil based-polyol / Aizatul Nabilla Zakwan - Zakwan, Aizatul Nabilla; Hirzin, Radin Siti Fazlina Nazrah (Universiti Teknologi MARA Shah Alam, 2022)
Raw materials for the production of polyurethane (PU), including polyols and isocyanate are derived from crude oils which pose multitude environmental impacts. While, the exploits of pure cooking oil, like palm oil used as a feedstock for polyol could cause bio-crisis, triggered by the imbalance of its demands and supplies. Hence, the utilization of vegetables or cooking oil from waste are mandatory to resolve the impacts. This study revolves around the comparative assessment of waste cooking oil (WCO) over pure cooking oil, as well as, the optimization of temperature, different acids and catalysts and hydrogen peroxide loading in the production polyol via epoxidation and hydroxylation reaction. An acid reacts with hydrogen peroxide, produces peroxy-acid and water, which then reacts with WCO, first step through the epoxidation process. Afterwards, to produce polyol the breaking of the epoxidized-ring fatty acids is carried out by the reaction of hydroxylation aided by catalyst i.e., hydrochloric acid, sulphuric acid or phosphoric acid. Notoriously, WCO have similar triglyceride structure as pure cooking oil. However, even after filtration, some factors have considerable effect on its fatty acid compositions such as duration of usage, exposure of temperature and type of food used during cooking. In regards to temperature when producing polyol, it is discovered that higher temperature led to more ring-opening, nonetheless, prolong high temperature causes more side reactions which is undesirable. Additionally, acetic acid has surpassing oxygen carrier properties over formic acid in epoxidation reaction. Alongside, sulphuric acid being the most efficient inorganic acid catalyst due to stronger acid exhibits profound ring-opening of epoxidized oil. Furthermore, higher loading of hydrogen peroxide is preferable. Lastly, variations of extraction of sustainable acids which can be used as oxygen carrier for epoxidation i.e., formic acid and acetic acid derived from empty fruit bunch and food wastes are also demonstrated.